A new class of polynomials and the polynomials related to them - Chandel, R. S.; Singh Chandel, R. C. (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
The present paper deals with the study of a general class of polynomials. We mention some particular cases deduce some of their properties.